An ageing well collaboration: opportunity or wicked problem. Issue 1 (30th November 2018) - Hazelton, Lois Marjorie; Gillin, Laurence Murray; Kerr, Fiona; Kitson, Alison; Lindsay, Noel
Abstract : Purpose: Within the "wicked" concept of ageing, this paper aims to primarily model an integrated approach to identifying and evaluating opportunities that deliver innovative outcomes in Ageing Well Practice, Health and Economic Policy and Research Actions using a collaborative and entrepreneurial mindset. The strategic focus is on a "Boomer" (user)-driven and facilitated Network – that brings together health professionals, research specialists, technologists, ageing well providers, "encore" career specialists, life-style providers, community groups, wealth creation specialists and industry innovators to streamline the progression of identified concepts to valued users and markets and enhance the economy. Design/methodology/approach: Using the unit of analysis for innovation, i.e. the "added-value" as perceived by the user and not simply a product or a technology, the identified "opportunity-outcome" will embed a new service concept or intervention, which embraces and promotes ageing well, independent living or resident-centred care in the community and delivers direct and indirect economic benefits. Findings: The authors model a point of differentiation in facilitating existing ageing well policies in the community, through a focus on an integrated and multi-dimensional collaborative framework that can deliver user value and contributes to community and economic benefits. Research limitations/implications: Generalising results without a commercial business case from this single strategic viewpoint requires caution. The positive outcomes from this innovation collaborative concept can be used to guide further policy development and business investment in ageing well needs. Practical implications: Such an integrated innovation collaborative structure provides the capacity to identify ageing well opportunities, to contract enterprises, both SMEs' and larger companies, for development of the opportunities into user-valued outcomes, to network venture resources and deliver these outcomes to a sustainable market of ageing well citizens. Social implications: The Ageing Well Innovation collaborative framework identifies practical ways to integrate new concepts of ageing participation to be realised by the increasing number of "Boomers". It provides a self-managing process for linking individuals, public and private parties to maximise information and ideas flow, and engagement of the skilled resources in the Boomer group. Originality/value: The innovation collaborative structure proposed is not simply novel but is a targeted focus on entrepreneurship and innovation applied strategically to the needs of ageing boomers and community needs. The added-value is in the demonstrated enhancement to effective innovation outcomes in community ageing and the economy.